1995
DOI: 10.1002/bit.260460612
|View full text |Cite
|
Sign up to set email alerts
|

Hyphal growth and fragmentation of Penicillium chrysogenum in submerged cultures

Abstract: A previously derived population model describing the average properties of hyphal elements in submerged cultures of filamentous fungi was revised, and a term for the influence fo spore germination on the average total hyphal length was added. The model was derived from a general balance for the distribution function for the hyphal elements. Based on experimental data and the derived model, simple kinetic expressions for spore germination, tip extension, branching, and hyphal break-up were set up. It is conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 15 publications
3
58
0
3
Order By: Relevance
“…In addition, the fullness and size of the hairy region of the pellet could be quantified, in a way similar to clump characterization for the dispersed form. Nielsen et al (1995) developed yet another semi-automatic image analysis method to study pellets, and demonstrated a relationship between the balance of pelleted and freely dispersed forms and penicillin production from P. chrysogenum.…”
Section: Pelleted Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fullness and size of the hairy region of the pellet could be quantified, in a way similar to clump characterization for the dispersed form. Nielsen et al (1995) developed yet another semi-automatic image analysis method to study pellets, and demonstrated a relationship between the balance of pelleted and freely dispersed forms and penicillin production from P. chrysogenum.…”
Section: Pelleted Morphologymentioning
confidence: 99%
“…It has been mentioned that Nielsen et al (1995) developed a method to characterize all of the forms they observed in P. chrysogenum fermentations. It should be noted that Justen et al (1996) used projected area to describe of the dispersed forms in their agitation trials.…”
Section: Pelleted Morphologymentioning
confidence: 99%
“…(1) (Nielsen & Krabben, 1995) (where k frag (z) is a rate constant ( µm − " h − "). When q frag is given by (1) a balance for the mean total hyphal length l t,av can be expressed as (Nielsen & Krabben, 1995) where n av is the mean number of actively growing tips and q tip (l t,av , z) is the mean tip-extension rate in the hyphal elements (m tip − " h − ").…”
Section: Methodsmentioning
confidence: 99%
“…
IntroductionThe autolysis taking place in submerged carbon-depleted cultures of Penicillium chrysogenum is influenced by numerous intrinsic (vacuolation, age-related hydrolase production, aging) and extrinsic (power input, shearing forces, nutrient and O 2 limitations, penicillin side-chain precursors) factors (Harvey et al, 1998;McIntyre et al, 1999McIntyre et al, , 2000Nielsen and Krabben, 1995;Paul et al, 1994;Paul and Thomas, 1996;Pócsi et al, 2000; Pusztahelyi et al, 1997a, b;White et al, 1999). In some aspects, the autolysis of P. chrysogenum is reminiscent of the apoptosis of higher eucaryotes under these conditions, e.g., it is an en- In carbon-depleted cultures of Penicillium chrysogenum, age-related chitinases were shown to play a crucial role in both autolysis and fragmentation as indicated by in vivo enzyme inhibition experiments using allosamidin.
…”
mentioning
confidence: 99%